Mapping the Future of Augmented Reality in 21st Century Education: A Comprehensive Bibliometric Review - Afdal Luthfi; Mukhlidi Muskhir; Hansi Effendi; Nizwardi Jalinus; Goncharova Maria Nikolaevna (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
Augmented Reality (AR) technology has emerged as a transformative tool in education, integrating digital information into the user's real-world environment. This study aims to explore global research trends in AR for education through bibliometric analysis. The primary objective is to identify the evolution of publications, influential sources, leading authors, and productive countries in AR research. Using data from Scopus (2020–2024), 1,232 documents were analyzed. The study reveals that the United States leads in research productivity, followed by China, Indonesia, Malaysia, and Germany. The research highlights the rising trend in AR publications, with annual growth rates of 23.15%. Key journals like "Education and Information Technologies" and "Education Sciences" are at the forefront, showcasing the interdisciplinary nature of AR in education. Prominent authors such as Archana Mantri and Liru Chen contribute significantly to the field. This research also identifies emerging trends in mobile applications, STEM education, and the integration of AR with virtual reality. Overall, bibliometric analysis provides a comprehensive understanding of AR’s impact, emerging research directions, and the global collaborative network, helping to guide future research and enhance AR’s integration in educational practices.